2013
DOI: 10.1159/000350213
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Real-World Use of Cinacalcet and Biochemical Response to Therapy in US Hemodialysis Patients

Abstract: Background/Aims: Data describing real-world use and effectiveness of cinacalcet are limited. We aimed to characterize predictors of treatment and changes in secondary hyperparathyroidism (SHPT) biochemistry after cinacalcet initiation. Methods: We studied 25,250 in-center hemodialysis patients from a large dialysis provider, alive through November 2004, with no prior cinacalcet prescription. Patients were followed until initiation of cinacalcet, censoring, death, or July 31, 2007. Initiators were further follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 21 publications
3
24
1
Order By: Relevance
“…The latter is plausible in that the EVOLVE Trial protocol specified titration of cinacalcet to a maximum daily dose of 180 mg during the first 20 weeks of the trial. Observational studies in which the dose of cinacalcet was recorded suggests that relatively few patients are titrated to doses .60 or 90 mg daily (7,20,21). The relative frequency of gastrointestinal side effects seen with cinacalcet therapy-principally nausea and vomitingmay be limiting the observed benefit, at least vis-à-vis parathyroidectomy-a potential example of efficacy versus effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is plausible in that the EVOLVE Trial protocol specified titration of cinacalcet to a maximum daily dose of 180 mg during the first 20 weeks of the trial. Observational studies in which the dose of cinacalcet was recorded suggests that relatively few patients are titrated to doses .60 or 90 mg daily (7,20,21). The relative frequency of gastrointestinal side effects seen with cinacalcet therapy-principally nausea and vomitingmay be limiting the observed benefit, at least vis-à-vis parathyroidectomy-a potential example of efficacy versus effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Etelcalcetide was approved by the US Food and Drug Administration in 2017 (15), and thus realworld utilization data are not yet suitable for analysis. Previous studies have identified patient characteristics that are associated with cinacalcet use; examples include more severe secondary hyperparathyroidism (higher PTH, calcium, and phosphate levels), longer dialysis vintage, younger age, black race, female sex, and comorbidities (16)(17)(18). However, there are no studies describing the distribution of calcimimetic use across facilities or assessing the extent to which patient and facility factors contribute to facility variation in calcimimetic use.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Interventional trials and noninterventional studies have shown that serum calcium reductions following cinacalcet initiation are common but typically occur without associated clinical manifestations. [12][13][14][15][16][17][18] However, there have been no large-scale investigations into the frequency, type, and effectiveness of clinical therapeutic intervention for patients who experience cinacalcet-induced calcium reductions.…”
Section: Introductionmentioning
confidence: 99%